Point-of-care ultrasound, today, tomorrow, and the future – the place for task sharing (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Maternal and neonatal morbidity and mortality remain public health concerns. A study onmortality in Kenyan hospitals found that neonates comprise two-thirds of deaths in the pediatric agegroup (0–13 years). These deaths are caused by preventable conditions or those, which can bemanaged better if diagnosed early, such as placenta insufficiency, placenta previa, severe fetal growthrestriction, congenital abnormalities, multiple pregnancies, and breech presentation; these can all beidentified using point-of-care ultrasound (POCUS). Obstetrical ultrasound availability is limited to level 4and higher facilities, yet most women access lower levels of health care. Implementation of POCUS iscurrently limited because of a lack of appropriate training, limited scope of practice for frontline workers,and legal framework.Objective: The POCUS project is being undertaken to develop national guidelines to facilitate the roll outand scale-up of obstetrical POCUS.Methods: A collaborative participatory approach is planned for the development of the national POCUSguidelines. The key in this process is the identification of suitable frontline workers who, with adjustmentto their scope of practice, appropriate training, implementation of a supervision/referral system, canundertake obstetrical POCUS and gain buy-in from regulatory bodies, the inclusion of voices of relevantstakeholders, and leadership from government. A landscape and stakeholders analysis will also beundertaken as part of the process of the guideline development.Results: Narrative literature review shows that the WHO recommends effective and reliable antenatalultrasound services to be available to all pregnant women to optimize maternal and newborn healthoutcomes and at least one ultrasound scan up to 24 weeks of pregnancy. That there are deliberateefforts in Kenya to introduce POCUS with pilot training and implementation. Where obstetrical POCUS isimplemented, it is useful in diagnosing fetal malpresentation, placenta previa, congenital malformations,or multiple pregnancies. Appropriate interventions, such as reduction of cesarean delivery, induction oflabor, reduction of small for gestational age, low birthweight, preterm birth, and stillbirths, can improve thehealth outcome of the mother and neonate. There is a need to develop national POCUS guidelines.Conclusions: Implementation of POCUS may be riddled with difficulties, particularly where frontlineworkers’ current scope of practice may not allow them to perform such procedures, regulatoryframework, lack of knowledge, awareness, negative attitude, or behavior. The proposed guidelines willaddress these barriers.